2019
DOI: 10.1007/s40119-019-00154-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiac Repolarization After Transcatheter Aortic Valve Implantation and Surgical Aortic Valve Replacement: A Longitudinal Study

Abstract: Introduction: Transcatheter aortic valve implantation (TAVI) has been established as an alternative to surgical aortic valve replacement (SAVR) for high-risk patients. To assess the impact of TAVI on cardiac repolarization, we compared QT dispersion (QTD) and the interval from the peak to the end of the T wave (Tpeak-Tend: TpTe) between the patients who underwent TAVI and those who underwent SAVR and TpTe between the patients who underwent TAVI or SAVR. Methods: This retrospective study was approved by the eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Contrary to most previously mentioned studies, Chino et al's study showed no significant changes in Tp-e, Tp-e/QT, and Tp-e/QTc after neither TAVI nor surgical aortic valve replacement [ 110 ].…”
Section: Resultsmentioning
confidence: 93%
“…Contrary to most previously mentioned studies, Chino et al's study showed no significant changes in Tp-e, Tp-e/QT, and Tp-e/QTc after neither TAVI nor surgical aortic valve replacement [ 110 ].…”
Section: Resultsmentioning
confidence: 93%